2018
DOI: 10.1103/physrevapplied.9.014028
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Supermode Dielectric Resonators for Axion Dark-Matter Haloscopes

Abstract: We present frequency tuning mechanisms for dielectric resonators, which undergo "super-mode" interactions as they tune. The tunable schemes are based on dielectric materials strategically placed inside traditional cylindrical resonant cavities, necessarily operating in Transverse Magnetic modes for use in axion haloscopes. The first technique is based on multiple dielectric disks with radii smaller than that of the cavity. The second scheme relies on hollow dielectric cylinders similar to a Bragg resonator, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…[91]. On the other hand, axion haloscope collaborations (ADMX [92][93][94], HAYSTAC [95][96][97], OR-GAN [98,99]) appear to have independently decided on the value ρ 0 = 0.45 GeV cm −3 .…”
Section: Local Dark Matter Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…[91]. On the other hand, axion haloscope collaborations (ADMX [92][93][94], HAYSTAC [95][96][97], OR-GAN [98,99]) appear to have independently decided on the value ρ 0 = 0.45 GeV cm −3 .…”
Section: Local Dark Matter Densitymentioning
confidence: 99%
“…To identify the frequency of the axion mass, m a , the experiment may either enforce some resonance or constructive interference condition for a signal oscillating at ω = m a (as in e.g. ADMX [93,94], MADMAX [177][178][179], HAYSTAC [95-97, 180, 181], CULTASK [182][183][184], Orpheus [185], ORGAN [98,99], KLASH [186] and RADES [187]), or be sensitive to a wide bandwidth of frequencies simultaneously (e.g. ABRACADABRA [21,188,189], BEAST [190] and DM-Radio [191]).…”
Section: Axion Haloscopesmentioning
confidence: 99%
“…The central problem in detecting the axion however is that we do not know the frequency, ω m a (1 + v 2 /2) at which the electromagnetic response to the axion field should be monitored. To search for this frequency, haloscopes either enforce a resonance or constructive interference condition for a signal oscillating at ∼ m a (as in e.g., ADMX [116,117], MADMAX [118,119], HAYSTAC [120][121][122][123], CULTASK [124][125][126], OR-GAN [127,128], KLASH [129] and RADES [130]), or are sensitive to a wide bandwidth of frequencies simultaneously (e.g., ABRACADABRA [131][132][133], BEAST [134] and DM-Radio [135]). See Ref.…”
Section: Axion Searchesmentioning
confidence: 99%
“…Recently, there was a study that showed a potential application of Bragg reflectors with a dielectric hollow using the TM 030 mode of cylindrical cavities [15]. The study presented a frequency tuning scheme which breaks the field symmetry along the cavity axis by splitting a dielectric cylindrical hollow in the longitudinal direction.…”
Section: Along the Longitudinal Directionmentioning
confidence: 99%
“…We modeled a cylindrical cavity with the same dimension as in Ref. [15] to reproduce the results for the longitudinal mechanism to check consistency. For each scheme, we introduced a tuning system with optimal dimensions and repeated the evaluation.…”
Section: Performance Comparisonmentioning
confidence: 99%